THE ECOSYSTEM OF ELECTRONIC CERTIFICATE IMPLEMENTATION IN ELECTRONIC COMMERCE SYSTEM - Ahmad Budi Setiawan (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2015)
The Trend of e-commerce in Indonesia is growing and developing rapidly. It is driven from demographic trends that exist in Indonesia. If the electronic transaction business can be well managed business that will be a huge benefit to the economy. Currently e-commerce ecosystem in Indonesia is still unfavorable. One of the obstacles in electronic transactions, namely related payments. This problem arises because the consumer electronics business in Indonesia has yet to feel the ease and security in electronic transactions that affect their beliefs and attitudes. Related to this, online businesses have started offering payment solutions that enable customers. Therefore it takes an electronic transaction conducive ecosystem to support such solutions. In this case the Government is obliged to facilitate electronic transactions conducive ecosystem. In addition, the implementation of the strategy also needed institutional electronic certificate to encourage the growth Ecosystem transasksi Electronic System Operator reliability and performance as well as facilitate the Government in managing electronic certificate policy. This study aims to provide advice to the government in the form of an implementation strategy ecosystems electronic transactions. The study was conducted using Soft System. Results of this study provide advice to the Government related to the availability of infrastructure and institutional electronic certificates in electronic transaction systems ecosystem as well as focus on the enforcement of existing regulations.Keywords: Electronic Certificate, e-commerce, Soft System